An Enhanced Power Spectral Density Transmissibility (EPSDT) approach for operational modal analysis: Theoretical and experimental investigation. (1st November 2015) - Yan, Wang-Ji; Ren, Wei-Xin
Highlights: A power spectral density transmissibility-driven fast-stabilizing approach is proposed. System poles are identified by employing the least-squares complex frequency-domain estimator. Asymptotic analysis is implemented to investigate the robustness to noise effect. Numerical and experimental examples are employed to demonstrate the efficiency and accuracy of the proposed method. Abstract: The transmissibility based operational modal analysis (TOMA) has drawn great attention due to its insensitivity to the nature of external excitation. Different from conventional modal identification approaches working in the frequency domain, it opens up a new path to find the system poles by utilizing mode shape information. Recently, the power spectral density transmissibility (PSDT) driven peak picking (PP) approach was proposed by authors for large-scale linear engineering structures under a single operational loading condition. As a nonparametric method, however, the PSDT-driven PP approach identifies natural frequencies by just observing signal-based features subjectively without fitting a parametric model. An enhanced PSDT approach is proposed in this study. The system poles are identified by employing the least-squares complex frequency-domain (LSCF) estimator, following which the mode shapes are evaluated by utilizing singular value decomposition (SVD) technique for PSDT matrix. As a result, a stabilization diagram containing the information of frequency, damping ratio and mode shape can be constructed to separate the stable system poles. Furthermore, the asymptotic analysis is implemented to investigate the robustness of PSDT to noise effect. The presented approach is able to maintain the benefits of PSDT and at the same time leads to an improvement of the modal parameter estimation. It is computationally efficient, simple, stable and robust to noise. A numerical example subjected to ground motion and two structures tested in the field are employed to demonstrate the efficiency and accuracy of the proposed method.